GAMBARAN SERTA KESESUAIAN TERAPI DIARE PADA PASIEN DIARE AKUT YANG MENJALANI RAWAT INAP DI RSUD SLEMAN - Jayanto, Imam; Ningrum, Vitarani Dwi Ananda; Wahyuni, Wahyuni (Sam Ratulangi University, 2020)
ABSTRACTDiarrhea defined as bowel movements that does not form or in a liquid consistency with increasingfrequency. According to the data of World Health Organization (WHO), diarrhea isthe number one cause of infant mortality in the world. This research aims to describe thepharmacological use of antidiarrheal therapy and rehydration in the management hospitalizeddiarrheal patients in Sleman District Hospital according with SPM in this case using the SPMSardjito Hospital, Yogyakarta. This research carried out with the observational analytic crosssectional design (cross-sectional) and a prospective collecting data on patients hospitalizeddiarrhea in Sleman District Hospital during June to September 2012. Sampling used purposivesampling techniques that meets inclusion criteria. Type of data in this research is secondarydata and primary data taken from the demographic data and patient medical records aswell as interviews with relevant patients. Analysis the research data done in 2 ways, that isusing descriptive analysis to describe the demographic distribution of diarrhea in SlemanDistrict Hospital. Then continued with the inferential analysis using SPSS test a logisticsBinner and chi-square test. The results are was 34% the suitability treatment in the form ofantibiotic therapy for diarrhea; was 16.68% in the form of diarrhea rehydration therapy; was100% in the form of antidiarrheal therapy.Keywords : Acute diarrhea, therapeutic efficacy, binary logisticABSTRAKDiare didefinisikan sebagai buang air besar yang tidak berbentuk atau dalamkonsistensi cair dengan frekuensi yang meningkat. Menurut data Badan Kesehatan Dunia(WHO), diare adalah penyebab nomor satu kematian balita di seluruh dunia. Penelitian inibertujuan untuk mengetahui gambaran terapi farmakologi penggunaan antidiare dan rehidrasidalam penanganan pasien diare rawat inap di RSUD Sleman dengan mengacu pada SPMRSUP Sardjito, Yogyakarta. Penelitian ini dilakukan secara observasional dengan rancangananalitik cross sectional (potong lintang) dan pengambilan data secara prospektif pada pasiendiare rawat inap di RSUD Sleman selama Juni – September 2012. Pengambilan sampelmenggunakan teknik purposive sampling yang telah memenuhi kriteria inklusi. Jenis datayang digunakan dalam penelitian ini adalah data sekunder dan data primer yang diambil daridata demografi dan data rekam medik pasien serta wawancara langsung dengan pasienterkait. Analisis data hasil penelitian dilakukan dengan 2 cara, yaitu memakai analisisdeskriptif untuk mengetahui gambaran distribusi demografi pasien diare di RSUD Sleman.Lalu dilanjutkan dengan analisis inferensial dengan memakai uji SPSS berupa logistik binnerdan uji chi-square. Hasilnya terdapat kesesuaian terapi sebesar 34% yang berupa terapiantibiotik untuk diare; sebesar 16,68% yang berupa terapi rehidrasi diare; sebesar 100% yangberupa terapi antidiare.Kata Kunci : Diare akut, kemanjuran terapi, logistik biner